Crise imanente e conflito social na metrópole de Belo Horizonte: reflexões a partir da questão da moradia, na Região da Izidora - Luiz Antonio Evangelista de Andrade (2017)
The initial perspective of this study concerns the approach to some of the social conflicts that has happened contemporaneously in the metropolis of Belo Horizonte, whose motivations, on a quick observation, refer the "housing theme". Among these conflicts, the one that has been most intensive in expressing such apparent motivations, in the last 10 or 12 years, is the appearing of urban occupations in various private and public lands, as in Belo Horizonte as metropolitan region. We approached the empirical and specific reality of three occupations: Vitória, Esperança e Rosa Leão. Gather, the three occupations have approximately 8000 families and are about of three years and eight months, at that which in the last great zone of Belo Horizonte. This empirical initial perspective, related the analysis of the claims of social movements, supporters and residents, which are in two central axes: 1) that is fulfilled the constitutional principle of social function of property and the social right at decent housing; 2) That housing theme is related to the topics of social justice and dignity of human person, contained at Federal Constitution of 1988. We search to relate the reflection about the housing theme with the critical of state political form and the juridical form, in their relationships with value form of the sociability that it produces and the specific historic form of domination that occurs around it. We search too connect this social forms and others fundamental socioeconomic categories with radical theory of crisis, to understand the particular social conflicts highlighted.